2019
DOI: 10.1371/journal.pone.0224032
|View full text |Cite
|
Sign up to set email alerts
|

Membrane associated proteins of two Trichomonas gallinae clones vary with the virulence

Abstract: Oropharyngeal avian trichomonosis is mainly caused by Trichomonas gallinae, a protozoan parasite that affects the upper digestive tract of birds. Lesions of the disease are characterized by severe inflammation which may result in fatality by starvation. Two genotypes of T. gallinae were found to be widely distributed in different bird species all over the world. Differences in the host distribution and association with lesions of both genotypes have been reported. However, so far no distinct virulence factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Additionally, differentially expressed proteins were identified from bovine and feline Tritrichomonas foetus genotypes, providing evidence of host-specific adaptation [28]. A recent comparative proteomic analysis of the membrane proteins has been carried out in another trichomonad Trichomonas gallinae, showing distinct proteins associated with virulence [29].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, differentially expressed proteins were identified from bovine and feline Tritrichomonas foetus genotypes, providing evidence of host-specific adaptation [28]. A recent comparative proteomic analysis of the membrane proteins has been carried out in another trichomonad Trichomonas gallinae, showing distinct proteins associated with virulence [29].…”
Section: Introductionmentioning
confidence: 99%
“…However, Amin et al ( 2012 ) found a correlation of peptidase activity and virulence in chicken liver cell culture and a recent study from Martínez-Herrero et al ( 2019 ) found that membrane-associated proteins vary with virulence and some of the identified proteins are described to be potential virulence factors, similar to their orthologs in T. vaginalis , yet the classification of trichomonad isolates as pathogenic or non-pathogenic is still mainly based on the severity of the symptoms induced in the host (Amin et al 2014 ). Our results indicate that the identification of virulent strains due to the widely used molecular markers does not seem sufficient and the susceptibility of the host seems to be an important factor to consider and studies might suffer from possible co-infections of different genotypes (Martínez-Herrero et al 2019 ). While we did not find a difference in virulence of single strains, being infected with more than one strain did increase the risk to develop clinical signs of trichomonosis in our study.…”
Section: Discussionmentioning
confidence: 95%
“…Even though genetic data indicate some variation between isolates, no correlation with virulence is yet established (Gerhold et al 2008;Grabensteiner et al 2010;Ecco et al 2012;Stimmelmayr et al 2012) and there is no molecular marker or molecular assay to distinguish virulent from non-virulent strains (Forrester and Foster 2008). However, Amin et al (2012) found a correlation of peptidase activity and virulence in chicken liver cell culture and a recent study from Martínez-Herrero et al (2019) found that membraneassociated proteins vary with virulence and some of the identified proteins are described to be potential virulence factors, similar to their orthologs in T. vaginalis, yet the classification of trichomonad isolates as pathogenic or non-pathogenic is still mainly based on the severity of the symptoms induced in the host (Amin et al 2014). Our results indicate that the identification of virulent strains due to the widely used molecular markers does not seem sufficient and the susceptibility of the host seems to be an important factor to consider and studies might suffer from possible co-infections of different genotypes (Martínez-Herrero et al 2019).…”
Section: Clinical Signsmentioning
confidence: 99%
“…Thus, we do not rule out the role of GP63-like metalloproteases in feline T. foetus infection. Additionally, in Trichomonas gallinarum, GP63-like and subtilisin-like proteases were proposed as virulence determinants 61 . In this context, we suggested a potential role of cysteine proteases (papain and calpain), serine proteases (subtilisin-like proteases) and metalloproteases (GP63-like) as pathogenic factors and potential biomarkers for feline T. foetus.…”
Section: Discussionmentioning
confidence: 99%